Landscape Based Agricultural Water Demand Modeling—A Tool for Water Management Decision Making in British Columbia, Canada - Neilsen, Denise; Bakker, Matthew; Van der Gulik, Ted; Smith, Scott; Cannon, Alex; Losso, Istvan; Warwick Sears, Anna (Frontiers in Environmental Science, 2018)
Regional water managers face challenges managing water demand and supply in response to climate change. In British Columbia (BC), < 5% of the total land surface is suitable for cultivation and consequently, urban development and agriculture co-exist on lower elevation sites and compete for water. Surface and ground water supply all uses, affecting in-stream habitats and aquifer levels. To assess water needs, we used a GIS-based water demand model for agricultural water use, with layers for detailed land use, soils, a digital elevation model, sub-basins, aquifers, and socio-political jurisdictional boundaries. The model was driven by gridded daily minimum and maximum temperatures and precipitation at a 500 m spatial resolution using historical data (1961–2010) and downscaled climate scenarios (1961–2100) derived from five CMIP5 climate models under two greenhouse gas concentration scenarios (RCP4.5 and RCP8.5). Two case studies were examined: Changes in water use were determined for scenarios of climate change and expanded cropping within the BC Agricultural Land Reserve for 17 agricultural regions. Potential increases in irrigation water demand (IWD) in response to climate change ranged from 21 to 58 and 30 to 114% under low and high emissions scenarios respectively. Land use change scenarios resulted in very large potential increases in water demand, up to 2,400%. Output from this work forms the basis for a web-based agricultural water license calculator. Effects of crop production systems on IWD were examined in the Okanagan region. Combinations of pasture and forage crops with inefficient irrigation systems were most vulnerable to drought as indicated by two indices: relative vulnerability index (IWD/ETo) and allocation vulnerability index (IWD/Maximum annual water allocation). In drought years, up to 70% of the irrigated area was vulnerable. A comparison of detailed land use surveys made in 2006 and 2014 indicated a large shift to highly efficient irrigation systems in the horticultural sector from 38 to 68% of the irrigated acreage. Similar shifts for other agricultural sectors may require financial support. On-going development of regional drought management will require collaborative decision making by water suppliers and users.